Penegakan Hukum Operasi Tertangkap Tangan Terhadap Tindak Pidana Korupsi Oleh Satuan Tugas Sapu Bersih Pungutan Liar: Studi Kasus No.58/Pid.Sus-TPK/2017/PN MDN - Fuji Sasmita; Ediwarman Ediwarman; Muhammad Hamdan; Edi Yunara (Universitas Sumatera Utara, 2019)
Abstract. Illegal fee is one of corruptions that widely happen in public administration both at central or regional levels. The government has formed Satuan Tugas Sapu Bersih Pungutan Liar to fight illegal fee with red-handed operation. This research tries to investigate some problem: the regulation about Satuan Tugas Sapu Bersih Pungutan Liar to do red-handed operation, constraining factors in red handed operation and law enforcement policy in case of Medan District Court number 58/Pid.Sus/TPK/2017/PN MDN. The method used in this research is normative and empirical research. The nature of the research is descriptive analysis. The type of data used is secondary data derived from primary, secondary, and tertiry legal material. Secondary data are collected by literature study technique and field study with data collection tool in the form of interview. Furthermore, the data are analyzed by using qualitative analysis method. The result of the research shows that the regulation about Satuan Tugas sapu Bersih Pungutan Liar in red-handed operation has been arranged on President Regulation number 87/2016 and Governour Decision number 188.44/181/KPTS/2018. Meanwhile, the constraining factors are limited funds, facilities, difficulty in obtaining the information, community participation, lack of socialization, and culture. Concerning the policy of law enforcement as showed by Medan District Court number 58/Pid.Sus-TPK/2017/PN MDN, is carried out analysis of the chronology of the case, the prosecutor’s charge, the prosecutor’s demand, the legal facts, the judge’s evidence, and the judge’s verdict. Based on the analysis of Medan District Court number 58/Pid.Sus-TPK/2017/PN MDN there is inaccurate application about law. The prosecutor demand the defendant ESS with article 11. According to this analysis that the defendant should be demanded and decidec by using article 12 e about extortion. Keywords: illegal fee , criminal act of corruption, red-handen operation